Estimation of acrylamide exposure in Italian schoolchildren consuming a canteen menu: health concern in three age groups. (2nd January 2020) - Branciari, Raffaella; Roila, Rossana; Ranucci, David; Altissimi, Maria Serena; Mercuri, Maria Lucia; Haouet, Naceur M.
Abstract: Acrylamide (AA) is a food process contaminant with carcinogenic and genotoxic properties that is formed in thermally treated foods, especially carbohydrate-rich. Dietary exposure to AA, due to school canteen foods, was estimated in schoolchildren aged 3–13 years by combining the AA concentration in foods with the amount and frequency of food consumption. Potato products and bakery products presented the highest mean levels of AA (841 and 244 µg/kg, respectively) followed by meat (222 µg/kg) and egg products (151 µg/kg). The mean total AA intake was estimated at 2.16 µg/kg bw/d, with the highest percentages provided by potato products (34.5%), meat products (26.1%) and bread (24.5%). The calculated margins of exposure (MOEs) for the average AA exposure (84 and 212 for the benchmark dose lower confidence limits (BMDL) of 0.17 and 0.43 mg/kg bw/d) suggest that there is a health concern with respect to students eating in school canteens.